Evaluating the performance of waqf land development: a case study of Wakaf Seetee Aisah, Pulau Pinang / Nur Afiqah Anuar ... [et al.] - Anuar, Nur Afiqah; Sulaiman, Muhammad Azwan; Mokhtar, Nor Nadirah Akmar; Zainol, Nurul Nadiah; Isa, Mona; Wan Yusoff, Wan Zahari (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Waqf commonly works to preserve a thing or an asset and maximize the benefits or revenues for the beneficiaries. In Malaysia, waqf matters are managed by institutions such as the State Islamic Religious Council, which acts as a trustee. This council will plan and manage the waqf land according to the specific deed, either for general or specific waqf deed, as prescribed by the person who waqf the asset. However, waqf lands are usually not fully utilized. The community may not notice or realize that development is taking place, thus affecting the performance of waqf land development This research aims to identify the current waqf land development in Pulau Pinang, determine the challenges faced by the State Islamic Religious Council of Pulau Pinang in developing Wakaf Seetee Aisah, and measure the performance of waqf land development at Wakaf Seetee Aisah in Pulau Pinang. To achieve the research objectives, a qualitative approach through a semi-structured interview was conducted with four professionals practicing waqf land development in Pulau Pinang. The data gathered was analyzed through a content analysis method that interprets the respondents' responses. The research shows that the performance of waqf land development in Wakaf Seetee Aisah is doing well. All the developed units are sold, and the rental income increases annually. However, the results found that administration and marketing efficiency can still be enhanced. Lastly, it is hoped that this study can provide insights for the State Islamic Religious Council to improve their practice in managing the waqf land development more efficiently